Behavioral and emotional problems in school children: teachers and parents perspective - Masare, Monika S.; Patale, Priti J.; Bansode–Gokhe, Seema S. (International Journal Of Community Medicine And Public Health, 2019)
Background: The present research was carried out with an objective to study the behavioral problems and emotional problems of school children as perceived by their parents and teachers. Methods: This cross sectional observational study was conducted on parents and teachers of 304 secondary school children of a metropolitan city. A pre formed semi structured questionnaire was used to assess the socio-demographic profile of the students. Parents and teachers rated Strength and difficulties questionnaire was used to assess their child’s /students behavioral and emotional problems as perceived by their parents & teachers. The analysis was done using Microsoft Excel and SPSS software. Results: Regarding the perception of teachers and parents it was found that parents were not much concerned as the response rate for parent reported SDQ was only 64.8% and response rate among teachers was 100%. Out of 304 study subjects, 22 (7.2%) were having borderline total difficulties on teachers reported total difficulty scale of SDQ and 11 (3.6%) were reported to be abnormal. Parent reported SDQ showed that out of 197 parents, who filled the SDQ, 24 (7.9%) study subjects were having borderline total difficulties, while 33 (10.9%) were found to be abnormal on SDQ scale. Conclusions: Parents, child-care givers, teachers and health care professionals if made aware of symptoms of mental health problems in their children’s, we can restore their mental health conditions in time.